Development of a Simple Data Logger using Seeeduino Stalker and the Data Visualization using Processing software - Dian Artanto; Yosef Capertino W. P.; Khriswara Dwitantyo (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
This paper presents the development of a simple data logger using Seeeduino Stalker and the data visualization using Processing software. The background of this development is the problems encountered in making a data logger, which must meet the following criteria: able to read data one or more sensors, able to store the data, able to be operated for a long time, even if placed in an area that has no electricity supply. In addition, the data that stored in the data logger should be loaded and displayed on a computer without having to stop the operation of the data logger. In this study, the data logger that meets these criteria has been developed using Seeeduino Stalker hardware and using Processing software for the data visualization.